Environmental assisted cracking in power plant / Zainuddin Yahya and Mustafa Bakri - Yahya, Zainuddin; Bakri, Mustafa (Faculty of Mechanical Engineering, 1999)
This project has expose students of engineering to understand the effect of environment to the material in a power plant. It also gives information and knowledge about types of environment assisted cracking and how it was initiated. From this information we may identify what kind of environment that influence the cracking of material in Stesen Janaelektrik Sultan Salahuddin Abdul Aziz (SJSSAA). A study at microstructure level was done on the sample of the roof of the fuel tank to see the differences under different environmental effect. Observation was done on the roof of the fuel tank and identification of surrounding environment also was carried out for example air quantity, temperature, temperature variation, humidity, rainfall, contaminants, and pollutants. We relate all these findings with theoretical to find the cause of environment assisted cracking in power plant.